Laser in Situ Keratomileusis for Moderate to High Myopia in Mongolians - Tsetsegjargal Baasanjav; Uranchimeg Davaatseren; Davaalkham Dambadarjaa; Baasankhuu Jamyanjav (Central Asian Journal of Medical Sciences, 2022)
Objectives: To compare the pre and post-operative outcomes of Mongolian patients who had LASIK surgery. Methods: We conducted hospital based prospective study. A total of 176 consecutive patients who underwent conventional LASIK were examined for the correction of myopia. Study participants were followed for 5 years after surgery. Results: The mean age was 29.89 ± 6.42 years. 145 patients were female and 31 were male. The mean UCVA was 0.10 ± 0.09 Decimal and the mean BCVA was 0.81 ± 0.16 Decimal. Preoperative analysis showed that UCVA and BCVA were significantly different in mild, moderate, and high myopia groups. Especially, patients with mild myopia had higher acuity compared to other groups (0.21 ± 0.13 and 0.86 ± 0.12, respectively). Moreover, the manifest spherical equivalent the of mild myopia group also had significantly lower compared to the other two groups (-1.73 ± 1.17). Conclusions: Our results support the view that preoperative clinical examination is an extremely important part of the LASIK procedure to improve refractive predictability.